Pengaruh Love of Money dan Trust on Government terhadap Kepatuhan Wajib Pajak - Azzahra, Azzahra; Helmy, Herlina (Universitas Negeri Padang, 2025)
This study aims to analyze the influence of love of money and trust in government on taxpayer compliance. The population is individual taxpayers in Padang. A convenience sampling technique was employed, resulting in a total of 400 respondents. The data utilized in this study are primary data, collected through a survey by distributing questionnaires via Google Forms. The data were analyzed using multiple linear regression with the assistance of SPSS version 25. The results indicate that: (1) love of money does not significantly affect taxpayer compliance, and (2) trust in government has a statistically significant positive impact on taxpayer compliance.